2012
DOI: 10.1016/j.ymgme.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

In utero copper treatment for Menkes disease associated with a severe ATP7A mutation

Abstract: Menkes disease is a lethal X-linked recessive neurodegenerative disorder of copper transport caused by mutations in ATP7A, which encodes a copper-transporting ATPase. Early postnatal treatment with copper injections often improves clinical outcomes in affected infants. While Menkes disease newborns appear normal neurologically, analyses of fetal tissues including placenta indicate abnormal copper distribution and suggest a prenatal onset of the metal transport defect. In an affected fetus whose parents found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Another MD patient with a mutation that resulted in no ATP7A protein on Western blotting died at 5.5 months despite very early copper treatment [10]. Although our patient’s current medical problems appear consistent with classic MD, his progressive development up until 8 months old, when he could control his head and sit with minimal assistance, in the absence of copper treatment, was atypical [7].…”
Section: Discussionmentioning
confidence: 86%
“…Another MD patient with a mutation that resulted in no ATP7A protein on Western blotting died at 5.5 months despite very early copper treatment [10]. Although our patient’s current medical problems appear consistent with classic MD, his progressive development up until 8 months old, when he could control his head and sit with minimal assistance, in the absence of copper treatment, was atypical [7].…”
Section: Discussionmentioning
confidence: 86%
“…Other ATP7A functions include removal of copper from cells across the plasma membrane in response to increases in its concentration, pumping copper into melanosomes for metalation of tyrosinase, contribution to axonal and synaptic development, and involvement in neuronal activation . Mutations in ATP7A , or its murine homolog, Atp7a , impair all these processes, with the defect in copper transfer to DBH resulting in distinctively abnormal neurochemical patterns, including markedly elevated ratios of non–beta‐hydroxylated to beta‐hydroxylated metabolites in the catecholamine biosynthetic pathway …”
Section: Discussionmentioning
confidence: 99%
“…The molecular characterization of Mo-dp null mutation and establishment of a genotyping assay for the Mo-dp allele facilitate these efforts. We previously showed that prenatal copper replacement alone in a human fetus with a severe loss of function mutation in ATP7A gene failed to rescue the phenotype [14]; thus we speculate that neonatal ATP7A gene addition plus subcutaneous copper injections represents a reasonable approach in such circumstances. Given the complete loss-of-function mutation in Atp7a , rescue of affected male Mo-dp mice by viral gene therapy would provide further proof of concept for this therapeutic approach in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Copper levels in fresh frozen brains were determined by graphite furnace atomic absorption and confirmed by inductively coupled plasma mass spectrometry, as previously described [14, 15]. …”
Section: Methodsmentioning
confidence: 99%